Carbohydrate dynamics in roots, stems, and branches after maintenance pruning in two common urban tree species of North America (2018)
The ability of plants to tolerate stress is determined in part by the carbon allocated to their reserves. We studied two common urban tree species in northeastern North America, Acer saccharinum (Silver maple, native) and Acer platanoides (Norway maple, exotic), to assess the dynamics of non-structural carbohydrate (NSC) concentrations immediately following a maintenance pruning of 30% of the tree crown. NSC concentrations were measured by high-performance liquid chromatography in branches, main stems, and root tissues for both pruned and un-pruned trees at three intervals during the growing season. NSC concentrations in tree organs of A. platanoides were 75% higher than in A. saccharinum. Maintenance pruning did not have any significant depletion effect on carbohydrate concentrations in the tissues of either species. Yet, there was a significant increase in the NSC concentrations in un-pruned branches of pruned trees of A. platanoides at the end of the growing season, but no effect was observed in A. saccharinum. Higher levels of carbohydrates after pruning in woody plant tissues suggested that A. platanoides may have compensatory mechanisms that allow this species to respond better to maintenance pruning than A. saccharinum. © 2018 Elsevier GmbH